A educação bilingue e o construtivismo sócio-cultural em contexto de ensino-aprendizagem em L1: Um estudo de caso das EPCs de Museveni, Tandara e Maxavelene - Machalele, Domingos Filipe (Multilingual Margins: A journal of multilingualism from the periphery, 2020)
One of the principles that guide the Bilingual Education program in Mozambique is that the school is more “an agent of transformation, than (…) a means of transmitting knowledge” (INDE /MINED, 2003:9). It means that the school must safeguard policies that allow the student to build his own knowledge, discussing, in a reflexive and critical way, what he learns and relating the school contents to his socio-cultural reality. It is based on this assumption that this paper discusses constructivist pedagogical practices in the context of teaching-learning in L1. For this purpose, I draw on Piaget (1983) and Vygotsky`s (1991) constructivist theory and on the concept of funds of knowledge. I also use the fundamental theory (Fortin, 1996) for the analysis of grade 2 and 3 class, the target groups in this study. In this paper, I argue that L1 serves as a facilitator for the link between funds of knowledge and formal knowledge and enhances the use of socio-constructivist pedagogical practices in the classroom.